2020
DOI: 10.1002/jbmr.4098
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Zoledronate Subsequent to Denosumab in Osteoporosis: a Randomized Trial

Abstract: Discontinuing denosumab is associated with bone loss and possibly increased fracture risk. We investigated if treatment with zoledronate (ZOL) could prevent bone loss and if the timing of the ZOL infusion influenced the outcome. We report on a 2-year randomized, open label, interventional study including 61 patients with osteopenia, discontinuing denosumab after 4.6 AE 1.6 years. We administrated ZOL 6 months (6M group, n = 20) or 9 months (9M group, n = 20) after the last denosumab injection or when bone turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 21 publications
6
74
1
3
Order By: Relevance
“…Recently, denosumab has received quite some attention due to general concerns about the so-called “rebound effect” observed after discontinuing treatment with denosumab. Especially after prolonged treatment [ 119 , 120 ], there are clinical concerns that treatment with the most potent bisphosphonate, zoledronic acid, is not sufficient to prevent the rapid bone loss observed after discontinuation of denosumab treatment [ 121 , 122 ]. In animal models of denosumab treatment, a rebound effect was observed after stopping OPG treatment resulting in the reformation of numerous osteoclasts [ 58 ], something which is supported by numerous reports on discontinuing denosumab treatment for patients [ 119 , 120 , 123 ].…”
Section: Implications For Physiology and Pathologymentioning
confidence: 99%
“…Recently, denosumab has received quite some attention due to general concerns about the so-called “rebound effect” observed after discontinuing treatment with denosumab. Especially after prolonged treatment [ 119 , 120 ], there are clinical concerns that treatment with the most potent bisphosphonate, zoledronic acid, is not sufficient to prevent the rapid bone loss observed after discontinuation of denosumab treatment [ 121 , 122 ]. In animal models of denosumab treatment, a rebound effect was observed after stopping OPG treatment resulting in the reformation of numerous osteoclasts [ 58 ], something which is supported by numerous reports on discontinuing denosumab treatment for patients [ 119 , 120 , 123 ].…”
Section: Implications For Physiology and Pathologymentioning
confidence: 99%
“…infusion of ZOL 5 mg, given 6 months after the last injection of denosumab therapy maintained for 3 years the BMD gains in the majority (around 80%) of patients previously treated with Dmab for an approximate period of 2.5 years [16]. On the contrary, treatment with ZOL, irrespective of the timing of administration, did not fully prevent bone loss among patients with an approximate 4.5 years of Dmab treatment [10]. Therefore, besides other yet unknown factors, Dmab treatment duration probably plays a role in the diversity of results among different studies.…”
Section: Discussionmentioning
confidence: 91%
“…Conventional thinking and the known retention of BPs in the skeleton support the notion of a possible protective effect against both bone loss and increased fracture risk from previous BP use as this could potentially blunt the rebound phenomenon. This, however, was not proved by a recent RCT, which included patients with an up to 3 years previous alendronate treatment or even longer treatment with any other BP [10], and a real-world observational study [11].…”
Section: Discussionmentioning
confidence: 95%
“…For over half of patients in this study who were started on denosumab, it was the first bone-health medication they were observed to take, despite it not being recommended as a first-line treatment in most cases [6-8, 21]. This recommendation is due in part to the cost of the medication but also due to the need to pre-screen for hypocalcaemia and co-morbidities and due to complications that arise with cessation of the drug [7, 21, 28]. This pattern of prescribing reflects findings from a large primary care study in Australia where denosumab went from making up a small percentage of bone-health prescriptions in 2012 to being the most frequently prescribed in 2017 [23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review including 16 studies of denosumab showed that average 2-year persistence was only 55% [14]. Treatment with oral bisphosphonates after stopping denosumab is protective against negative effects in most patients after one year of treatment, however stronger replacement treatments may be required for patients taking denosumab for longer periods [21, 22].…”
Section: Introductionmentioning
confidence: 99%